(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Inclusive education represents one of the central humanistic directions in modern pedagogy, emphasizing equal access to learning and holistic development of all children, regardless of physical, intellectual, or social differences. The concept of upbringing (moral and value-based education) within inclusive education extends beyond mere academic inclusion—it involves nurturing empathy, social responsibility, communication skills, and respect for diversity. This article examines the theoretical, psychological, and pedagogical foundations of upbringing in inclusive settings, explores challenges faced by teachers and students, and suggests practical strategies for fostering moral, emotional, and social development among diverse learners.